2015
DOI: 10.1021/acs.jpca.5b09191
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Investigation of the Radical–Radical Reaction of O(3P) + C2H3 and Comparison with Gas-Phase Crossed-Beam Experiments

Abstract: Herein, we present an ab initio study of the prototypal radical-radical reactions of ground-state atomic oxygen [O((3)P)] with the vinyl (C2H3) radical using density functional theory and a complete basis set model. Two distinctive pathways on the lowest doublet potential energy surfaces (PESs) were predicted to be in competition: addition and abstraction. The barrierless addition of O((3)P) to the hydrocarbon radicals leads to energy-rich intermediate formation followed by subsequent isomerization and decompo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…2012; Jung et al . 2015). We believe these reactions can occur at low temperature, under 0 °C and the resulting intermediates can be stable until the contact with some components of the primordial atmosphere (water, carbon dioxide, ammonia, hydrogen sulphide and methane) when in favourable thermodynamic conditions they will form simultaneously proteinogenic amino acids and the corresponding polypeptides.…”
Section: Resultsmentioning
confidence: 99%
“…2012; Jung et al . 2015). We believe these reactions can occur at low temperature, under 0 °C and the resulting intermediates can be stable until the contact with some components of the primordial atmosphere (water, carbon dioxide, ammonia, hydrogen sulphide and methane) when in favourable thermodynamic conditions they will form simultaneously proteinogenic amino acids and the corresponding polypeptides.…”
Section: Resultsmentioning
confidence: 99%
“…The 38 Se-Hee indicates the possibility of CH 2 COH formed by CHC and H 2 O. CH 2 COH generates two different products CH 3 CO and CH 2 CHO through the isomerization reaction. 39 In the process of dissociation of acetaldehyde, Han found that CH 3 CO and CH 2 CHO can generate acetaldehyde through hydrogenation. 40 In addition, the possibility that acetaldehyde can be formed by a combination of vinyl and water is also speculated.…”
Section: Dft Calculation Of the Benzenementioning
confidence: 99%
“…We must note that in this study we calculated the enthalpies of formation and Gibbs free energies only for reactions apparently without transition state [14][15][16][17], which result at low temperatures. For the reactions occurring at contact with atmospheric primary components that may require activations too, reactions which occur at higher temperatures, we have mentioned only the reaction enthalpies.…”
Section: Reactionsmentioning
confidence: 99%
“…It was considered that all reactions after which the derivative precursors of aziridinone would get, at low temperatures, would form only by reactions resulting after the photochemical reactions model [13], it means that in their way from initial states to final states we would have to do only with a decreasing in energies of involved reaction systems [14][15][16][17]. In more drastically thermodynamic conditions, reactions between precursors and primary atmospheric components would be produced.…”
Section: Introductionmentioning
confidence: 99%